Tissue engineering : engineering principles for the design of replacement organs and tissues - Saltzman, W. Mark (OUP E-Books., 2004)
Tissue engineering is a field of biomedical engineering, in which synthetic materials are used together with biological components such as tissue fragments, cells, proteins to encourage tissue regeneration, regrowth, and repair. Intended for engineering students, this book introduces the principles of tissue engineering.